2006
DOI: 10.1021/es0517670
|View full text |Cite
|
Sign up to set email alerts
|

Using Size Fractionation and Pb Isotopes to Study Pb Transport in the Waters of an Organic-Rich Upland Catchment

Abstract: Processes controlling Pb release from a small organic-rich upland catchment in northeast Scotland were investigated via measurement of Pb concentrations and 206Pb/207Pb ratios in rainwater, throughflow, surface flow, and receiving streamwaters under storm and baseflow conditions. For this catchment, the output of Pb via streams was only 2.0 +/- 1.2 kg year(-1) (11.4 +/- 6.8 g ha(-1) year(-1)), much lower than the input of 7.5 +/- 2.0 kg year(-1) (42.6 +/- 11.4 g ha(-1) year(-1)), and so the catchment is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
(47 reference statements)
6
36
0
Order By: Relevance
“…With the exception of Pb in the porewaters of S3 and the bottom section of S5, both Pb and Fe were almost exclusively present in the colloidal fraction, These results are consistent with previously published work (e.g. Graham et al, 2006;Schroth et al, 2008) showing that Pb solubility is enhanced by association with both organic and Fe-rich colloids.…”
Section: Bcr Sequential Extraction Of Selected Soil Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…With the exception of Pb in the porewaters of S3 and the bottom section of S5, both Pb and Fe were almost exclusively present in the colloidal fraction, These results are consistent with previously published work (e.g. Graham et al, 2006;Schroth et al, 2008) showing that Pb solubility is enhanced by association with both organic and Fe-rich colloids.…”
Section: Bcr Sequential Extraction Of Selected Soil Samplessupporting
confidence: 92%
“…For example, several studies have shown significant binding of Sb to soil humic acids (Buschmann and Sigg, 2004), whilst others found only limited organic complexation within soils (Filella, 2011). Lead has been shown to be largely immobile in upland organic-rich soils in NE Scotland but during storm events it can be released in association with organic-rich colloids (Graham et al, 2006). A recent study also showed that phase associations of Pb were influenced by soil pH with significant adsorption to organic matter at pH <5 but preferential adsorption to Fe (oxy)hydroxides at higher pH (Shi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of considering time, distance, and isotopic composition when studying lead in lake sediments, peat, boreal forest soils, and the overlying vegetation has been central to research done by our group at Umeå University and quite a number of other groups working elsewhere in Europe (e.g., Bacon et al 1995Bacon et al , 1996Farmer et al 1996;Shotyk et al 1998;Weiss et al 1999;Farmer et al 2002;Le Roux et al 2005;Steinnes et al 2005b;Bacon et al 2006;Graham et al 2006;Cloy et al 2008) and North America (e.g., Kaste et al 2003;Watmough et al 2004;Watmough and Dillon 2007). Based on these results, as I will summarize later, Patterson's estimate in 1965 of a 1,000-fold increase in atmospheric levels of lead as compared to the natural environment has proved fairly accurate for remote areas removed from emission point sources but exposed to long-range sources and diffuse local/ regional atmospheric sources (e.g., car and industrial emissions).…”
Section: Introductionmentioning
confidence: 99%
“…Given the intensity and extent of atmospheric Pb pollution, there is ongoing interest in the fate of anthropogenic Pb in forest soils throughout the temperate zone of the northern hemisphere (Siccama et al, 1980;Dö rr and Mü nnich, 1989;Dö rr et al, 1990;Friedland et al, 1992;Miller and Friedland, 1994;Johnson et al, 1995;Wang et al, 1995;Wang and Benoit, 1996;Wang and Benoit, 1997;Brännvall et al, 2001b;Semlali et al, 2001;Kaste et al, 2003;Semlali et al, 2004;Klaminder et al, 2008a,b;Kylander et al, 2008). One approach to understanding the transformations and fate of Pb in soils is to study the streams which drain their respective watersheds (LaZerte et al, 1989;Erel et al, 1990Erel et al, , 1991Patterson, 1992, 1994;Tarvainen et al, 1997;Outridge, 2000;Emmanuel and Erel, 2002;Vinogradoff et al, 2005;Graham et al, 2006;Klaminder et al, 2006;Bindler et al, 2008b;Bur et al, 2009;Landre et al, 2009). Concentrations of total dissolved Pb in natural waters may be very low (Hirao and Patterson, 1974;Erel et al, 1991), with values reported for surface waters (Field and Sherrell, 2003) and recent groundwaters (Shotyk et al, 2010) below 1 ng/L.…”
Section: Introductionmentioning
confidence: 99%